Diseño de una lechada de cemento espumado, como base para una cementación primaria, para yacimientos con bajos gradientes de fractura (2018)
In this project the design of a foamed cement slurry is developed as the basis for a primary cementation, at laboratory scale for the study well, which has a low fracture gradient in the production zone. The project aims to compare the properties, advantages and differences of an ultralight cement with microspheres and a foamed one; taking into account that the formulation of the slurry was made for a highly depleted, fractured and with low fracture gradient.